Characterization of trusted masks on the market, physically - Bambang Murdaka Eka Jati; Miranda Putri Saraswati (Journal of Physics: Theories and Applications, 2025)
A study was conducted to physically characterize masks that have been accepted in Indonesian market. This was motivated by the importance of masks as part of public health measures, preventing droplets from the wearer from leaving the mask and from outside (other people) from entering the mask, while maintaining a comfortable breathing environment. The purpose of this study was to physically characterize the three layers (front, middle, and back) of the mask. The results of this study can serve as a reference for small businesses in producing masks that are suitable for use. The research method was carried out in three stages. Stage 1: Calibration of the red and green laser wavelengths used, using diffraction grating (250, 500, and 750 lines/mm). Stage 2: Randomly selected masks from several reputable brands on the market. The lattice constants of the front and back layers of the masks, as well as the water absorption of the middle layer, were measured. This was done (on single brand of mask) in new, used, and used condition with treatment (washing and ironing). Stage 3, checked the lattice constant value (distance between the front and back layer pores) which was seen with microscope (with a micrometer installed in it) at a magnification of 83,3 times. The results obtained were the lattice constant value of the front and back layers and water absorption in the middle layer respectively: (a) new mask: (3.1  0.1)x10-3 cm; (1.3  0.2)x10-3 cm, and (3  1)x10-1 g/minute; (b) used mask: (1.3  0.4)x10-3 cm, (1.2  0.4)x10-3 cm, and (3  1)x10-1 g/minute; (c) used mask with treatment: (1.4  0.4)x10-3 cm, (1.4  0.3)x10-3 cm, and (14  1)x10-1 g/minute. Visual observations using a microscope yielded a lattice constant equivalence to the laser diffraction method. These results indicate that, regardless of comfort, mask suitable for use do not have to be new but this also applies to used masks that have been treated.